2015
DOI: 10.1007/s10162-015-0533-9
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the Human Frequency Following Response for Carrier and Modulation Frequency Assessed Using Adaptation

Abstract: The frequency following response (FFR) is a scalp-recorded measure of phase-locked brainstem activity to stimulus-related periodicities. Three experiments investigated the specificity of the FFR for carrier and modulation frequency using adaptation. FFR waveforms evoked by alternating-polarity stimuli were averaged for each polarity and added, to enhance envelope, or subtracted, to enhance temporal fine structure information. The first experiment investigated peristimulus adaptation of the FFR for pure and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
(75 reference statements)
6
11
0
Order By: Relevance
“…They attributed the reduction in the amplitude of the FFR over time to the adaptation of neurons generating the response. Result of the present study was comparable to findings reported by (Gockel et al, 2013;Gockel et al, 2015), where both investigations showed greater amplitude for the FFR at earlier time intervals and a reduction 1 2 in its amplitude over time over time. Therefore, reduced amplitude in the left ear could be attributed to a decrease in neural activity over time due to the adaptation of neurons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They attributed the reduction in the amplitude of the FFR over time to the adaptation of neurons generating the response. Result of the present study was comparable to findings reported by (Gockel et al, 2013;Gockel et al, 2015), where both investigations showed greater amplitude for the FFR at earlier time intervals and a reduction 1 2 in its amplitude over time over time. Therefore, reduced amplitude in the left ear could be attributed to a decrease in neural activity over time due to the adaptation of neurons.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the amplitude of the FFR in the left ear was reduced compared to the right ear. Secondly, the reduced amplitude of the FFR in the left ear could be a consequence of the reduction in the neural firing rate over time due to adaptation of neurons contributing to the generation of the FFR (Gockel et al, 2013;Gockel et al, 2015). In the present study, the response of right and left ears were obtained at time intervals between 10 msec and 60 msec and 110 msec and 160 msec post stimulus onset, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…The goal of a study by Gockel et al [44] was to determine the characteristic frequency of neurons from which the FFR originates. This was explored using the phenomenon of adaptation, namely the decline of the FFR in response to a steady stimulus.…”
Section: Frequency Specificity Of the Ffr Assessed Using Adaptationmentioning
confidence: 99%
“…Gockel et al [44] measured the FFR for a 100-ms pure tone target (T) that was preceded by a 200-ms pure tone adaptor (A) with either the same or different frequency as T. A and T either had a low frequency (L) of 213 Hz (presented at 80 dB SPL) or a high frequency (H) of 504 Hz (presented at 75 dB SPL), and they were combined in an orthogonal design, leading to four conditions (ALTL, ALTH, AHTL, and AHTH). The FFR was analyzed for five different 50-ms time windows: three over the time course of the adaptor, and two over the time course of the target (see caption of Fig.…”
Section: Frequency Specificity Of the Ffr Assessed Using Adaptationmentioning
confidence: 99%
“…These simple stimuli are often unnatural, but they allow for precise manipulation of the acoustic cues. Examples are tonebursts (Clinard et al, 2010; Gardi et al, 1979; Glaser et al, 1976; Tichko and Skoe, 2017), pure tones (Gockel et al, 2015; Holmes et al, 2018), tone sweeps (Billings et al, 2019; Clinard and Cotter, 2015; Krishnan and Parkinson, 2000; Purcell et al, 2004) and (sinusoidally) amplitude modulated (AM) stimuli (Bidelman and Patro, 2016; Dimitrijevic et al, 2016; Van Canneyt et al, 2019). It is unclear whether findings for these non-speech stimuli can be generalized to responses evoked by speech stimuli.…”
Section: Introductionmentioning
confidence: 99%